Technical climate change adaptation options of the major ski resorts in Bulgaria - Demiroglu, O.C.; Turp, M.T.; Ozturk, T.; An, N.; Kurnaz, M.L. (Springer International Publishing, 2016)
Climate change has been and increasingly will be a major threat to the ski tourism industry, whose survival is highly dependent on the existence of snow cover of sufficient depth and duration. For this matter, it is even now more usual for the ski resorts to adapt to this issue by various measures at the technical, operational, and political levels. Technically speaking, snowmaking has become the method most used throughout the industry to combat the immediate impacts of climate change, while moving the ski areas to higher terrains has been standing out as an another option, wherever available and feasible. In this study, the aim is to project the future climatic changes in snowmaking capacity; in other words, technical snow reliability, and the moving requirements, if any, of the four major ski resorts in Bulgaria for the period of 2016-2030 with respect to the control period of 1991- 2005. For this purpose, the past and the future climatic conditions for the technical snow reliability of the ski resorts and their immediate surroundings are determined by the temperature and the relative humidity values generated and projected through the Regional Climate Model RegCM 4.4 of the Abdus Salam International Centre for Theoretical Physics (ICTP) by scaling the global climate model MPI-ESM-MR of Max Planck Institute for Meteorology down to a resolution of 10 km. The model is further processed according to the recent RCP 4.5 and RCP 8.5 concentration scenarios of the IPCC. The model outputs on air temperature and relative humidity are utilized for determination of wet-bulb temperatures through psychographic conversions that ultimately provide us with thresholds for snowmaking limits. Findings display the temporal changes in the snowmaking hours of the ski resorts at various altitudinal levels calculated according to the environmental lapse rates. Such displays can guide the practitioners in considering investment lives and moving the ski resorts according to optimistic and pessimistic projections. © Springer International Publishing Switzerland 2016.
Keywords: Bulgaria; Climate Change; Climate Modeling; Ski Area Extension/Expansion; Snowmaking